The Communism as Forbidden Ideology - Yuniarti, Endah (Journal of Innovation in Teaching and Instructional Media, 2024)
Communism has unfortunately had a bad reputation in Indonesia as a result of the tendency to blend this ideology with political elements. This is particularly apparent in the process of selecting a party chairperson in Indonesia, in which the Statute/Articles of Association of any party indirectly implied that communism is a forbidden ideology. Therefore, the notion that communism is an unacceptable ideology could easily emerge among the members of society. This paper shows that Communism has in fact no significant correlation in the process of selecting the chairperson of a political party. The process of selecting the chairperson of a political party will not run in a democratic way if the Statute/Articles of Association of a political party did not obtain previous legalization of the Government.